Evaluation of the use of intrauterine device Lipper as a method of family planning - Vicuña Ríos, Juan (2015)
The results of using large Lippes Loop in 436 patients from a Family Planning Center of Lima are presented. 5.384 months of use were tabulated. 10 unintended pregnancies (failure rate 2.21) two of them were seen unnoticed IUD expulsion The main adverse effects were vaginal discharge, pelvic pain and vaginal bleeding; the incidence of expulsions was lower than that reported in the publications. It has removed the D.I.U. by pelvic infection in 1.4% of patients. Has not been observed uterine perforation, IUD translocation or malignancy of exfoliative cytology. With an average of 12.4 months using woman there, a dropout rate of 38.8%. These results are discussed in comparison with international experiences. Finally statistical data showing that the motivation of the patient by the method increases with age and parity, parallel however increase the incidence of undesirable effects thereof are presented.